2016
DOI: 10.1007/s10649-016-9727-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing a deeper understanding of mathematics teaching expertise: an examination of three Chinese mathematics teachers’ resource systems as windows into their work and expertise

Abstract: In order to develop a deeper understanding of mathematics teaching expertise, in this study we use the Documentational Approach to Didactics to explore the resource systems of three Chinese mathematics Bexpert^teachers. Exploiting the Western and Eastern literature we examine the notion of Bmathematics teaching expertise^, as it is perceived in the East and the West. The data consist of two rounds of in-depth interviews, observations and teachers' representations of their resource systems, where teachers descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
1
27
0
3
Order By: Relevance
“…Their analyses of particular United States programs led them to observe, however, that the programs analyzed apparently offered "few changes to the underlying opportunities for teaching and learning found in print materials", and "the use of multimedia in particular lacked interactivity." This rings true for our research on e-textbooks (e.g., Gueudet et al 2017;Pepin et al 2016), where we observed that more connections of different kinds could be made in existing e-textbooks.…”
Section: Teacher Interaction With Traditional and Digital Curriculum supporting
confidence: 55%
See 1 more Smart Citation
“…Their analyses of particular United States programs led them to observe, however, that the programs analyzed apparently offered "few changes to the underlying opportunities for teaching and learning found in print materials", and "the use of multimedia in particular lacked interactivity." This rings true for our research on e-textbooks (e.g., Gueudet et al 2017;Pepin et al 2016), where we observed that more connections of different kinds could be made in existing e-textbooks.…”
Section: Teacher Interaction With Traditional and Digital Curriculum supporting
confidence: 55%
“…Drawing on two different collective environments and two individual teacher cases working within these environments, we investigate and illustrate teachers' design processes and design capacity building across a range of contexts and curriculum formations, with the focus on how digital resources can help to develop teacher design capacity. We claim that the evolutions of digital resources in particular require an elaboration and 1 3 curriculum expertise, individually when preparing their lessons, and collectively in professional development sessions and other interactions with their colleagues (e.g., Pepin et al 2016). Moreover, the collective dimension is an important aspect of teachers' professional development and capacity building (e.g., Jaworski 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Scientists focus attention on the fact that school students' future life depends on this examination, therefore, only experienced teachers are engaged in examination preparation (Pepin et al, 2017). During the whole year, school students write weekly mathematics tests, thereby preparing only for examinations, practically they do not study new material.…”
Section: Analysis Of Foreign Researchesmentioning
confidence: 99%
“…If the students could achieve the learning goals through a particular teaching approach, then the approach can be regarded as good [1]. One of the mathematics leaning goals is to create what the students learn become meaningful [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, representation becomes important since mathematics teachers cannot bring the mathematics object in front of their students [4,5]. Furthermore, the idea of reducing the abstract sense in mathematics learning has been massively promoted to help students understand the mathematics concepts better [1,2,6,5,[7][8][9]. Therefore, they need manipulatives to show what the objects look like and what properties attached to the objects.…”
Section: Introductionmentioning
confidence: 99%